The Use of Information Technology and its Impact on The Efficiency of Modern Management Accounting Methods in Jordanian Government Institutions in the Time Period 2022-2023 - Almalkawi, Majdi Mohammad Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
The Study Aimed to know the use of Information Technology in Jordanian Governmental Institutions and its Impact on the Efficiency of Modern Management Accounting Methods in Jordanian Governmental Institutions. To Achieve this, the Researcher relied on two measures, the first dealing with the Variables of the study. The study sample amounted to 307 employees in those institutions, and the statistical analytical program spss was used. The results showed that the degree of both the variable of use of information technology and the variable of efficiency of modern administrative accounting methods was high, and that there was a significant effect of the variable of use of information technology on all dimensions of the variable of modern administrative accounting methods in the study sample, and no statistically significant differences appeared for the use of information technology on The efficiency of modern management accounting methods in Jordanian government institutions is due to personal information (academic qualification, number of years of experience, job position). The Study Recommends the Necessity of Preparing and Training Employees Working in Government Institutions on a Mechanism to Keep Pace with new Accounting Methods Programs.